1993
DOI: 10.1515/jbcpp.1993.4.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ventricular Fibrillation Threshold During Acute Hypothermia. A Model for Future Studies

Abstract: Hypothermia and rewarming are associated with an increased incidence of lethal arrhythmias in man. The relationship between reduction in body temperature and ventricular fibrillation threshold was studied in 7 pentobarbital anaesthetized dogs using programmable electrical stimulation while cooling and rewarming between 37 degrees C and 25 degrees C in steps of 3 degrees C. Fibrillation threshold was defined as the number of extrastimuli required to evoke ventricular fibrillation. QRS-durations and corrected QT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…Most previous studies in humans and animals have shown that hypothermia is associated with increased susceptibility for ventricular arrhythmias and VF (18,23), and this effect has been related to the slowing of conduction, a heterogeneous increase in ventricular repolarization and the dispersion of refractoriness (21). However, there is experimental evidence suggesting the antiarrhythmic therapeutic potential of hypothermia (7,10).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies in humans and animals have shown that hypothermia is associated with increased susceptibility for ventricular arrhythmias and VF (18,23), and this effect has been related to the slowing of conduction, a heterogeneous increase in ventricular repolarization and the dispersion of refractoriness (21). However, there is experimental evidence suggesting the antiarrhythmic therapeutic potential of hypothermia (7,10).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, swine anaesthetized with medetomidineketamine-fentanyl showed a substantially higher incidence of ischaemia-induced ventricular brillation than swine anaesthetized with pentobarbital. This nding cannot be ascribed to differences in known determinants of ischaemia-induced ventricular brillation such as pre-ischaemic heart rate (Wainwright & Parratt 1993), body temperature (Mouritzen & Andersen 1966, Mortensen et al 1993, size of ischaemic area (Verdouw & Hartog 1986), collateral blood ow (Yoshida & Downey 1986, von Mutius et al 1988, and arterial pH (Dong et al 1967). A positive correlation between pre-ischaemic heart rate and occurrence of VF during ischaemia has been shown in swine (Wainwright & Parratt 1993).…”
Section: Discussionmentioning
confidence: 99%
“…maximum rate of phase 0 of the action potential, the conduction velocity, the peak potentials reached during depolarization (19,27,28,31), and the delayed rectifier and inwardly rectifying potassium currents (10,15,27). Hypothermia is associated with an increased susceptibility for ventricular arrhythmias and ventricular fibrillation (VF) (2,19,20,30,31), and this effect has been related to slowing of conduction, a heterogeneous increase in ventricular repolarization, and the dispersion of refractoriness (25,29).…”
mentioning
confidence: 99%
“…Hypothermia is associated with an increased susceptibility for ventricular arrhythmias and ventricular fibrillation (VF) (2,19,20,30,31), and this effect has been related to slowing of conduction, a heterogeneous increase in ventricular repolarization, and the dispersion of refractoriness (25,29). On the other hand, myocardial cooling has also been used to modify different cardiac rhythm disturbances.…”
mentioning
confidence: 99%
See 1 more Smart Citation